2020
DOI: 10.18632/aging.103327
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyelephantopin induces apoptosis via oxidative stress and enhances gemcitabine sensitivity in vitro and in vivo through targeting the NF-κB signaling pathway in pancreatic cancer

Abstract: Pancreatic cancer is a highly invasive malignant tumor of the digestive system with an unfavorable prognosis worldwide. This trait is thought to be largely attributed to chemoresistance. Chemotherapy is the only hope for patients with advanced pancreatic cancer. Therefore, seeking new effective chemotherapy drugs has become an urgent need. The purpose of our study was to explore whether deoxyelephantopin (DET), a sesquiterpene lactone, has a potential antitumor effect in pancreatic cancer. Additionally, the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The potential antitumor effect in pancreatic cancer of deoxyelephantopin (DET) ( 7 ), a natural sesquiterpene lactone isolated from the Chinese herbal medicine Elephantopus scaber (Asteraceae), was evaluated by Ji et al [ 98 ]. The antitumor effects of DET were evaluated alone and in combination with gemcitabine.…”
Section: In Vitro and In Vivo Bioactive Sesquiterpene Lactones With A...mentioning
confidence: 99%
“…The potential antitumor effect in pancreatic cancer of deoxyelephantopin (DET) ( 7 ), a natural sesquiterpene lactone isolated from the Chinese herbal medicine Elephantopus scaber (Asteraceae), was evaluated by Ji et al [ 98 ]. The antitumor effects of DET were evaluated alone and in combination with gemcitabine.…”
Section: In Vitro and In Vivo Bioactive Sesquiterpene Lactones With A...mentioning
confidence: 99%
“…DET has been demonstrated to induce intrinsic apoptosis in many types of cancer cell lines, including human osteosarcoma, pancreatic cancer, cervical cancer, breast cancer, lung cancer, nasopharyngeal cancer, colorectal cancer, and liver cancer cell lines through Bcl-2 family protein modulation. DET dose-dependently induces apoptosis through increased levels of pro-apoptosis Bax and decreased levels of anti-apoptosis Bcl-2, with the resultant activation of caspase-9, caspase-3, cytochrome c release, and PARP cleavage in human osteosarcoma cell lines, MG-63 and U2OS (4, 8, 16, and 32 µM) [ 71 ], and human pancreatic cancer cell lines, BxPC-3 (30 and 50 µM) and CFPAC-1 (40 and 60 µM) [ 72 ]. Similarly, Chim-Kei Chan et al has reported that DET (0.75, 1.5, and 3.0 µg/mL) induced a concentration-dependent upregulation of cleaved caspase-3 and cleaved PARP protein expression in HCT116 cells [ 34 ].…”
Section: Effect Of Det and Idet On Apoptosis Pathwaysmentioning
confidence: 99%
“…In BxPC-3 and CFPAC-1 cells, ROS generation was induced as early as 0.5 h, and reached its maximum level at 2 and 3 h of DET incubation (50 and 60 µM, respectively). DET dissipated ΔΨm, modulated the GSH/GSSG ratio, and depleted Trx activity in BxPC-3 cells (DET at 30 and 50 µM) and CFPAC-1 cells (DET at 40 and 60 µM) [ 72 ]. DET (2 mg/mL) induced c-Jun N-terminal kinase (JNK) activation through ROS generation, causing cell death in TS/A cells.…”
Section: Effect Of Det and Idet On Apoptosis Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…We next set out to test if BdS could extend olaparib usage by other mechanisms. For example, ATL, a sesquiterpene lactone reminiscent in structure to IJ-5 and BdS (Figure 1C), can increase ROS levels in a number of transformed cell lines, which could explain the increased BdS sensitivity of Kuramochi cells given their pre-existing replication stress vulnerability (Figure 2C) [14,[38][39][40][41]. Importantly, the increased ROS levels induced by ATL can lead to oxidative DNA damage, marked particularly by the formation of the DNA base oxidation product 8-oxo-7,8-dihydroguanine (8-OxoG), which triggers the induction of base excision repair (BER) [14].…”
Section: Bds Synergises With Olaparib To Induce Dna Damage In P53 Wildtype Cancer Cellsmentioning
confidence: 99%